Gigatonne Carbon Dioxide Removal: Reversing Global Heating Trends - Valone, Thomas F. (Research Advances in Environment, Geography and Earth Science Vol. 3, 2024)
The present study highlights about implementation of gigatonne carbon dioxide removal technologies. The inextricably tight connection between global CO2 values and global temperature, delineated and publicized by James Hansen and others, will finally create an urgency in the minds and hearts of all people so that global atmospheric carbon capture by the gigaton can begin in earnest and in parallel with carbon-free fuels, zero carbon emissions, renewable energy, and even negative carbon emissions, implemented worldwide. It is a surprising realization to many that a changing temperature tightly correlates with the carbon dioxide (CO2) levels worldwide in a linear, lockstep manner with a reversible but very short temporal feedback loop of only a few decades. A mapping of the past 400,000 years of earth’s climate history by Hansen, based on the Vostok ice core sampling, offers a glimpse into this remarkably tight relationship between CO2 and global temperature levels but also the average sea level over four ice ages that are clearly delineated in his historic depiction of all three quantities. As his Table accompanying the graph is analyzed, an equation linking the three variables has now been generated, yielding a fresh view into how past decades of hundreds of gigatons of atmospheric increase will continue to affect a worldwide temperature rise, also called “global warming.” Such an examination inevitably leads to the conclusion that the true cause of the global "heat-trapping effect" in physics is the current stored CO2 level, which exceeds that of 1950 by a factor of over 40%. (Note: This article uses both US tons and metric tonnes, which equals 0.907). The research presented in this review highlights the role of CO2's heat-trapping ability as the primary cause of the global warming trend. It also predicts the amount of additional heat that the Earth will experience if current trends continue, given that CO2 levels are over 40% higher than they have been in over 400,000 years. The proposed solution offered in this review is to initiate a 40 gigatonne carbon dioxide removal (CDR) annually in order to stabilize atmospheric CO2, followed by an expanded CDR effort toward a goal of 100 gigatonnes/year to begin reversing and lowering global temperature. The process can be scaled up and may someday offer a novel and inexpensive method for capturing billions of tons of atmospheric carbon that can immediately begin the reversal of the temperature and CO2 relationship that is so tightly correlated. In that way, more time could be allowed for the world to convert to 100% renewable energy and thus begin to drastically reduce its carbon emissions.